2002
DOI: 10.1021/jp0135205
|View full text |Cite
|
Sign up to set email alerts
|

Intracluster Ion−Molecule Reactions of Ti+with Methanol Clusters

Abstract: The intracluster ion-molecule reactions occurring within the titanium/methanol heterocluster ions are studied using a simple cluster source based on the mixing of the laser-ablated plasma with the supersonic expansion of a methanol vapor seeded in Ar carrier gas. The product ions are detected using a reflectron time-of-flight mass spectrometer. The mass spectra exhibit a major sequence of cluster ions with the formula Ti + (CH 3 O) 2 (CH 3 -OH) n , which are attributed to the hydrogen elimination reactions (-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 44 publications
(90 reference statements)
2
20
1
Order By: Relevance
“…8,11,12 The observation of peaks corresponding to TiO + indicated that the reaction was initiated by the insertion of Ti + into the C=O bond of an acetone molecule. We postulate that product formation proceeded through the reactions given below.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…8,11,12 The observation of peaks corresponding to TiO + indicated that the reaction was initiated by the insertion of Ti + into the C=O bond of an acetone molecule. We postulate that product formation proceeded through the reactions given below.…”
Section: Resultsmentioning
confidence: 99%
“…The experimental details of the ion-molecule reaction dynamics measurements have been described previously; [8][9][10] therefore, only a brief description is given here. Ti + ions were generated by focusing the third harmonic (355 nm) of a Nd:YAG laser onto a rotating titanium disk, with an illumination area of diameter ~0.5 mm.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations